Internationalization of Social Enterprise: Scaling Up the Social Innovation in Indonesia - Hery Pratono, A; Marciano, D; ., Suyanto; Gyo Jeong, B (KnE Social Sciences, 2018)
This study aims to understand how the internationalization of social enterprise occurs with support from the international non-profit organizations by interorganizational learning. The case study in Indonesia was undertaken to understand the transformation of non-profit and charity organizations, which adopt the concept of social enterprises from their international partners. To understand the interorganizational learning, this study used an interpretive research strategy, which was designed to examine how people make sense of their major life experiences that leads them. The findings indicate the process of inter-organizational learning from network selection to a value distribution in which the action part of the breakthrough innovation process is a cycle leading to the implementation of knowledge. The adoption of social enterprise principles in social innovation is a signal of movement from talking to action by developing and deploying innovative business models. Keywords: social enterprise, internationalization, inter-organizational learning